Clinical Characteristic of Elderly Patients with Insulin-Dependent Diabetes Mellitus - Yamato, Eiji; Cha, Tepyon; Ikegami, Hiroshi; Tahara, Yasuhiro; Ogihara, Toshio; Kawaguchi, Yoshihiko; Fukuda, Masahiro (Nihon Rōnen Igakkai zasshi, 1992)
The number of elderly patients with insulin-dependent diabetes mellitus (IDDM) is increasing because of the prolongation of life due to the improvement of diabetic control. For better management of elderly patients with IDDM, we investigated the clinical and genetic characteristic of older patients with IDDM in comparison with younger patients. The subjects studied consisted of 19 patients with IDDM treated at the Department of Geriatric Medicine, Osaka University Hospital. Among the 19 subjects, 7 patients (37%) were more than 50 years old, including 3 patients (16%) more than 65 years old. The clinical and genetic characteristics of these 7 patients (older patients group) were compared with those of 12 patients (younger patient group) whose age was less than 50 years old. The age at onset of IDDM was significantly higher in older patient group (46±13 years old; mean±SD) than in younger patient group (34±6 years old). There was no significant difference in the duration of IDDM between older and younger patients (13±6 and 12±8 years, respectively). There were no significant differences in daily insulin dose, glycemic control (fasting plasma glucose and HbA1c levels) and glycemic stability as measured by the standard deviation of 10 measured fasting plasma glucose levels between the two groups. The frequency of diabetic retinopathy and neuropathy in the older patients was slightly, but not significantly, higher than that in younger patients. The frequency of diabetic nephropathy was similar in both groups. Residual B-cell functions assessed by serum C-peptide response to intravenous glucagon and by urinary C-peptide excretion showed no difference between the two groups. The frequency of HLA-haplotypes was similar between the two groups, and all patients had DR4-DQA1*0301-DQB1*0401 or DR9-DQA1*0301-DQB1*0303 haplotype. We conclude that older patients with IDDM do not have a longer duration of the disease, but have a later onset of the disease than younger patients with IDDM, and that other clinical and genetic characteristics were not different between the groups.